Combining 2D and 3D Fundamentals to Foster Systems Thinking in Design Students: Reflections and Case Studies from an Interdisciplinary Design Degree - Smith-Harvey, James; Bahho, Mazin; Kelly, Roger; Chiappin, Anthony (Revista GEMInIS, 2022)
This paper proposes some interdisciplinary design education approaches which can help to introduce students to more holistic perspectives of design practice, the world, and the influence of design within it. Through reflection on our design education practice, the authors highlight particular benefits of integrative design pedagogy to increase student awareness of relationships between disciplines, systems thinking, ability to design for ‘synergy’, and to more adequately prepare designers for an increasingly interconnected and changing world. Case study as a qualitative methodology is utilised to reflect on our interdisciplinary design studio educational practice (Baskarada, 2014; Rashid et al., 2019). Reflective practice methodology is also used to critically reflect on the design education case studies (Brookfield, 2000; Osterman, 1990). Key findings from these case studies suggest that teaching both 2D and 3D design fundamentals in combination, and having real world projects, can give students more awareness of the interrelatedness of design disciplines and foster systems thinking from early in their design studies/careers. Non-assessed collaboration between students from different programmes also needs to be encouraged and facilitated. Introducing critical reflective approaches are also important, to give learners deeper understandings of the implications of design and the importance of designing to counteract ‘wicked problems’.